The Novels of Claude Simon - Loubère, J. A. E. (Cornell University Press, 2019)
This lucid and illuminating study traces the development of an extraordinary experimental writer from his earliest work of the 1940's to his most recent fiction. Ms. Loubère assesses Simon's aims and achievements, and parallels his development as a novelist to the development of the modern novel itself, showing how both moved from traditionalist forms and material toward the highly idiosyncratic "New Novel." After discussing his early works, she devotes a chapter each to Le Vent, L'Herbe, La Route des Flandres, Le Palace, Histoire, La Bataille de Pharsale, Les Corps conducteurs, and Triptyque. Step by step, she points out the changes in technique and focus that occur in each succeeding novel as Simon rejects conventional forms and introduces new ones.